HUBUNGAN INDEKS MASSA TUBUH DENGAN SIKLUS MENSTRUASI PADA MAHASISWA PSKPS ULM ANGKATAN 2019-2021 - Cibro, Impana; Kaidah, Siti; Marisa, Dona; Asnawati, Asnawati; Sanyoto, Didik Dwi (Homeostasis, 2023)
The menstrual cycle is the distance from the first day of menstruation in one month to the following month. This is influenced by several things, one of which is the body mass index. This study aims to explain the relationship between body mass index and the menstrual cycle in PSKPS ULM student class of 2019-2021. This research was carried out using the analytic observational method with a cross-sectional approach on 113 PSKPS ULM student class of 2019-2021. The sampling technique was carried out using the total sampling method where all respondents who met the inclusion criteria were used as research subjects. Subjects were asked to fill out a research questionnaire online via the Google form. 70 people (61.9%) had normal BMI, 43 people (38.1%) had abnormal BMI, 92 people (81.4%) had regular menstrual cycles and 21 people (18.6%) irregular. Of the 70 people with normal BMI, 59 people had regular menstrual cycles, and 11 people had irregular cycles. Of the 43 people with abnormal BMI, 32 people had regular menstrual cycles, and 10 people had irregular menstrual cycles. Data analysis used the chi square statistical test. The results of the data analysis showed that there was no relationship between body mass index and the menstrual cycle in PSKPS ULM student class of 2019-2021 (p=0.272).